Taxonomy and Phylogeny of Eight New Acrophialophora Species (Sordariales, Chaetomiaceae) from China - Lan Peng; Yan-Wei Zhang; Hai-Yan Wang; Chun-Bo Dong; Wan-Hao Chen; Jian-Dong Liang; Yan-Feng Han (Journal of Fungi, 2023)
The genus Acrophialophora belongs to the family Chaetomiaceae. With the addition of new species and transferred species from other genera, the genus Acrophialophora has expanded. In this study, eight new species related to Acrophialophora were isolated from soil samples in China. Using muti-locus phylogenetic (ITS, LSU, tub2 and RPB2) analysis combined with morphological characteristics, eight new species (Acrophialophora curvata, A. fujianensis, A. guangdongensis, A. longicatenata, A. minuta, A. multiforma, A. rhombica, and A. yunnanensis) are described. Descriptions, illustrations, and notes of the new species are also provided.